The roots of Ukrainian nationalism : Galicia as Ukraine's Piedmont - Magocsi, Paul R. (University of Toronto Press, 2002)
This study provides a solid background for understanding nineteenth-century Galicia as the historic Piedmont of the Ukrainian national revival.
Keywords: Ukrainians -- Galicia (Poland and Ukraine) -- History.; Nationalism -- Ukraine -- History.; Galicia (Poland and Ukraine) -- History -- Autonomy and independence movements.; Ukrainiens -- Galicie (Pologne et Ukraine) -- Histoire.; Nationalisme -- Ukraine -- Histoire.; Galicie (Pologne et Ukraine) -- Histoire -- Autonomie et mouvements indépendantistes.; HISTORY -- Europe -- Eastern.; HISTORY -- Europe -- Former Soviet Republics.; HISTORY -- Europe -- Russia & the Former Soviet Union.; Autonomy and independence movements; Nationalism; Ukrainians; Europe -- Galicia; Ukraine; Electronic books.; History